The Impact of Islamic Education on Students' Spiritual Well-being and Academic Performance - Nur Rois Nur Rois; Mansata Indah Maratona; Endri Puji Winaryo; Alfiatun; Lila Rahmawati (CV. Kalimasada Group, 2025)
The purpose of this research is to examine the impact of Islamic education on students' spiritual well-being and academic performance. This study seeks to understand how the values, teachings, and practices embedded in Islamic education contribute not only to students’ spiritual growth but also to their overall academic achievement. Using a mixed-method approach, the research combines quantitative data collected through surveys and academic records with qualitative insights from interviews and observations. The findings reveal that Islamic education significantly enhances students' spiritual well-being by fostering values such as sincerity, discipline, and responsibility. Moreover, these spiritual dimensions positively correlate with improved academic performance, particularly in areas such as motivation, self-regulation, and perseverance in learning. The results also indicate that students who actively engage in Islamic learning activities tend to demonstrate stronger moral character and academic resilience. This study highlights the essential role of Islamic education in shaping holistic student development, integrating spiritual maturity with intellectual excellence. Keywords: Islamic education, spiritual well-being, academic performance, students, holistic development